L’égalité de l’Esprit Saint au Fils et au Père d’après Didyme l’Aveugle - Grzywaczewski, Joseph (Vox Patrum, 2016)
The article presents Didymus the Blind’s teaching on the Holy Spirit. It is to be noticed that continues and develops the principles of Saint Athanasius’ pneumatology. Didymus rejects the opinion of the tropiko… that the Holy Spirit belongs to the created beings. Didymus underlines that the Spirit is equal to the Son and the Father, and consequently He belongs to the Holy Trinity. The Spirit is holy, but He did not receive His holiness; He has wisdom, but he did not receive it from anybody; He knows everything without learning. There is no change in the nature of the Holy Spirit. Holiness and wisdom and other qualities belong to His nature. He possesses them eternally and He cannot lose them. The Father and the Son and the Holy Spirit possess the same substance within the Trinity, but their missions are different. The three Divine Persons operate together ad extra, i.e. outside of the Trinity for the salvation of the people.